2021
DOI: 10.1017/jfm.2021.845
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a highly decelerated axisymmetric turbulent boundary layer

Abstract: Experiments were performed over a body of revolution at a length-based Reynolds number of 1.9 million. While the lateral curvature parameters are moderate ( $\delta /r_s < 2, r_s^+>500$ , where $\delta$ is the boundary layer thickness and r s is the radius of curvature), the pressure gradient is increasingly adverse ( $\beta _{C} \in [5 \text {--} 18]$ where $\beta_{C}$ is Clauser’s p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…They proposed scaling parameters based on this idea of an embedded shear layer and obtained self-similar mean velocity and Reynolds stress profiles in their large-defect APG TBL, as well as in other large-defect cases. Balantrapu et al (2021) also obtained self-similar profiles with the same scaling in their highly decelerated axisymmetric turbulent boundary layer. However, Maciel et al (2017a) noted that they could not find any roller-like structures that are the sign of a Kelvin-Helmholtz type instability.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…They proposed scaling parameters based on this idea of an embedded shear layer and obtained self-similar mean velocity and Reynolds stress profiles in their large-defect APG TBL, as well as in other large-defect cases. Balantrapu et al (2021) also obtained self-similar profiles with the same scaling in their highly decelerated axisymmetric turbulent boundary layer. However, Maciel et al (2017a) noted that they could not find any roller-like structures that are the sign of a Kelvin-Helmholtz type instability.…”
Section: Introductionmentioning
confidence: 64%
“…Balantrapu et al. (2021) also obtained self-similar profiles with the same scaling in their highly decelerated axisymmetric turbulent boundary layer. However, Maciel et al.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The object of our research is to provide an understanding of the strong APG axisymmetric boundary layers, in particular of the turbulence structure and the associated wall-pressure fluctuations. The companion paper (Balantrapu et al (2021), hereafter referred to as BHAD) presents the measurements of the mean flow and turbulence structure of a boundary layer over a body of revolution. BHAD found that the axisymmetric boundary layer behaved as if there is an embedded shear layer in the outer region.…”
Section: Introductionmentioning
confidence: 99%